Vključevanje študentov s posebnimi potrebami v visokošolsko izobraževanje - Vrhovski Mohorič, Mojca (Šolsko polje, 2007)
Within the concern for a more equal, harmonious, effective and more just social organization there is also the concern regarding the integration of persons with special needs into the school and broader social environment. Consequently, in recent decades, an increase in the number and presence of persons with special needs in educational institutions and in the entire society can be observed in most of the European Union states and also elsewhere, where foundations and conditions of integration are well established. According to the individual data, it is similar also with the number of students with special needs in institutions of higher education, but the increase is noticeable in more developed European states, where the provision of necessary adjustments in studies are well taken care of by a series of measures (with legislation, system solutions, strategic financing and suitable innovative and flexible strategies for the formation of an appropriate approach). In the paper, we compare some of the developed and developing higher education systems in various countries (Slovenia, Ireland, Germany, Slovakia, Great Britain, USA) according to law, regulations, rules, entrance procedures, adjustments and forms of counseling and support during studies. We find that especially those with long-term and good practice are developing numerous effective measures and strategies for the arrangement of accessible study to students with special needs, who should of course be givenmore emphasis and attention in our system of higher education as well. For students with special needs, unlimited entrance to study is provided in Slovenia, but they are less provided with special adjustments, help and counseling, and are therefore left to their own ingenuity, will and the help of those close to them. Practice and experience from abroad dictate it is good to develop the system integrally, proactively, innovatively and collaboratively and perhaps a step further that that, which is determined and enabled by the legislation.
Keywords: inkluzija; integracija; študentje s posebnimi potrebami; visokošolsko izobraževanje; vzgoja in izobraževanje